Optimalisasi Kinerja Perusahaan: Interaksi Pengungkapan Keberlanjutan dan Intellectual Capital dengan Keunggulan Kompetitif sebagai Pemoderasi - Chairunnisa, Nurlaila Maysaroh; Murwaningsari, Etty (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
This research investigates the influence of sustainability disclosure and intellectual capital on company performance, while also assessing the moderating role of competitive advantage in this relationship. The study focuses on energy sector companies listed on the IDX from 2019 to 2023, utilizing unbalanced panel data encompassing 210 company-year observations. The findings reveal that sustainability disclosure positively impacts company performance, whereas intellectual capital has no significant effect. Furthermore, competitive advantage does not moderate the relationship between sustainability disclosure, intellectual capital, and company performance.